STUDY THE EFFECT OF LYCOPENE EXTRACT AND NANO-LYCOPENE EXTRACTED FROM TOMATO WASTE IN INHIBITING MICROBIAL GROWTH AND AS AN INTIOXIDANT - Rasheed , Abd Al-Hussain Attia Ali; Al-Anbari, Iman Hameed (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2025)
This study was aimed to investigate effectiveness of lycopene and nano-lycopene extracted from tomato waste powder in inhibiting the growth of microorganisms was studied. The study included preparing lycopene extract using a triple solvent mixture (hexane, acetone, and ethanol) in ratios (2:1:1) after evaporating them from the extractor and using it to prepare nano-lycopene by the technique of High-energy mechanical grinding. The surface morphology and roughness of the lycopene nanoparticles was determined, and their dimensions were determined using an atomic force microscope (AFM).The effectiveness of both lycopene and nano-lycopene extract was tested to inhibit gram-positive and negative bacteria, fungi, and yeast using the suitable diffusion method at concentrations of (50, 100, 150, 200, and 250) micrograms/ml. Its antioxidant activity was studied using the DPPH method and compared to lycopene extract and industrial antioxidant.